Sovereign Debt Sustainability - Cash, Daniel (Taylor & Francis, 2022)
In 2020, the G20 proposed a solution for the debt-related issues affecting the world’s poorest countries due to the COVID-19 pandemic. However, their initiatives have failed to meet their objectives. The author argues that the reason for this failure is the inability to bring sovereign countries to the table to re-negotiate their debt agreements with private creditors as they fear credit rating agencies and the prospect of a downgrade. The author refers to this as the ‘credit rating impasse’.